The new economic mind : the social psychology of economic behaviour - Lewis, Alan; Webley, Paul; Furnham, Adrian (New York : Harvester Wheatsheaf, 1995)
Economics
2003-04-16
Keywords: Economics - Psychological aspects; Social psychology; Economic behaviour